RISK TAKING ATTITUDES AMONG PERSONS WHO RECEIVED AN AMYLOID PET SCAN AND THEIR CARE PARTNERS. (11th November 2018) - Jutkowitz, E; Van Houtven, C; Plassman, B L; Mor, V
Abstract: We used the CARE IDEAS data to investigate risk preferences among persons who had an Amyloid PET scan and their care partners. Dyads were asked: "Suppose there is a new technology that can return your [patient's name] memory to normal but has a risk of death. What is the highest risk of death–if any–that you [patient] would be willing to accept for this treatment? The number you give can be between 0%-100%." We examined the relationship between a scan result and preferences for the hypothetical treatment, and if a patient/care partner dyad agreed in their assessments. We estimated multivariable models controlling for dyads' demographics/socioeconomics, relationship, numeracy, and the patients cognitive impairment. In preliminary findings, scan results are not associated with patient risk preference. Risk taking differed by the patient's cognitive impairment. More severe patient cognitive impairment was associated with care partners overestimating the patient's willingness to accept risk.